Physiotherapy in Bangladesh: Inequality Begets Inequality - Firoz Ahmed Mamin; Rieke Hayes (Frontiers Media S.A., 2018)
BackgroundThe demand for health services in developing countries often outweighs provision. This article describes the present condition of physiotherapy in Bangladesh. Physiotherapy is not recognized as a profession by the government. There is no single registration and regulation body. The health-related and economic benefits of physiotherapy are not felt by the majority of Bangladeshi citizens.Areas coveredThe burden of disease is changing, and Bangladesh needs a profession that specializes in physical rehabilitation to face these challenges. This article outlines the benefits to patients and the wider economy from a broad physiotherapy regime for all Bangladeshi citizens. It describes the many barriers the profession faces.ConclusionPhysiotherapy is efficacious in many post-trauma situations and long-term conditions. Economic evidence supports the provision physiotherapy as a cost-effective treatment which should be considered as part of the provision of a universal health-care service. Official recognition of the protected "physiotherapist" title and a single registration and regulation agency are recommended.